Research on Recognition Algorithm of important Nodes in Complex Network - Su, Yue (Informatica, 2020)
It is very important to identify the important nodes in the network. On the basis of K-shell algorithm, this study studied the recognition of important nodes in complex networks. Firstly, this study introduced concepts of edge weight and influence coefficient, designed an IKS algorithm, and analyzed its recognition effect in Zachary network and real micro blog network. It was found from the experimental results that the partition results of the K-shell algorithm were coarse, while the partition results of the IKS algorithm were refined; the IKS algorithm could sort the important nodes accurately on the basis of the K-shell algorithm, and its rationality was higher than that of closeness centralization and PaperRank algorithm. The partition results in microblog network also verified the effectiveness of the improved method. The experimental results show that the IKS algorithm is reliable in the important node identification, which makes some contributions to the recognition of important nodes in complex network.